2015
DOI: 10.3920/bm2014.0162
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a yogurt matrix and cell microencapsulation on the survival of Lactobacillus reuteri in three in vitro gastric digestion procedures

Abstract: The goal of this study was to assess the interaction between microencapsulation and a yogurt food matrix on the survival of Lactobacillus reuteri NCIMB 30242 in four different in vitro systems that simulate a gastric environment. The four systems were: United States Pharmacopeia (USP) solutions, a static two-step (STS) procedure which included simulated food ingredients, a constantly dynamic digestion procedure (IViDiS), as well a multi-step dynamic digestion scheme (S'IViDiS). The pH profiles of the various p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…All the obtained results indicate the importance of using flaxseed mucilage for the formation of increased resistance of LAB cells. These data are consistent with the results of a study using polysaccharide-alginate to protect probiotic cells [68]. Providing an LAB survival of at least 10 6 CFU/mL during passage through the human gastrointestinal tract is desirable for health benefits [69].…”
Section: Discussionsupporting
confidence: 86%
“…All the obtained results indicate the importance of using flaxseed mucilage for the formation of increased resistance of LAB cells. These data are consistent with the results of a study using polysaccharide-alginate to protect probiotic cells [68]. Providing an LAB survival of at least 10 6 CFU/mL during passage through the human gastrointestinal tract is desirable for health benefits [69].…”
Section: Discussionsupporting
confidence: 86%
“…Data from our laboratory, where four in-vitro methods were compared (Champagne et al, 2015b), show that in-vitro methodologies strongly influence viability results of probiotic bacteria, which strongly limit comparisons between data in the literature. Data from our laboratory, where four in-vitro methods were compared (Champagne et al, 2015b), show that in-vitro methodologies strongly influence viability results of probiotic bacteria, which strongly limit comparisons between data in the literature.…”
Section: Simulated Git Conditionsmentioning
confidence: 99%
“…The interaction between probiotics and its dairy food matrix (most commonly yogurt and kefir) may beneficially modulate the symptoms of gastrointestinal distress such as diarrhea and constipation in a strain-dependent fashion [ 35 ]. In vitro research has shown that the unique viscosity of yogurt enhances the viability of probiotics by protecting it during simulated oral, gastric, and intestinal digestion [ 39 , 40 ]. Other mechanisms of improved probiotic survivability when consumed as part of yogurt have been proposed, such as the contributions of the yogurt to buffering stomach acidity, protection within the gastrointestinal tract through lactic acid bacteria–derived exopolysaccharides or MFGM, and the presence of lactose as an energy source for the probiotics [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%